Retrospective analysis of the long-term therapeutic effectiveness and safety profile of rituximab in the treatment of mucous membrane pemphigoid in a German university center between 2008 and 2019 - Bamberger, Florian; König, Inke R.; Gola, Damian; Zillikens, Detlef; Sadik, Christian D. (Frontiers in Immunology, 2023)
Background The B-cell-depleting anti-CD20 antibody rituximab (RTX) is often used as an adjuvant drug for the treatment of refractory cases of mucous membrane pemphigoid (MMP). Objective This study aims to determine the therapeutic effectiveness and the safety profile of RTX in MMP. Methods The medical records of all cases of MMP treated with RTX between 2008 and 2019 in our university medical center located in northern Germany, which specialized in autoimmune blistering skin diseases, were retrieved and systemically analyzed for treatment responses and potential adverse events over a median period of 27 months. Results We identified 18 MMP patients who received at least one cycle of RTX to treat MMP. RTX was always used as an adjuvant treatment, and its application did not change concomitant treatments. Under treatment with RTX, 67% of the patients achieved an improvement in their disease activity within 6 months. This was also reflected in a statistically significant reduction in the Mucous Membrane Pemphigoid Disease Index (MMPDAI) activity score. The frequency of infections under RTX treatment increased only slightly. Conclusions The use of RTX is associated with an attenuation of MMP in a large proportion of MMP patients in our study. At the same time, its application was not found to further increase the susceptibility of the most strongly immunocompromised population of MMP patients to opportunistic infections. Collectively, our results suggest that the potential benefits of RTX outweigh its risks in patients with refractory MMP.